Enhancement of reinforced concrete durability and performance by bamboo and basalt fibres - Diana, Mohamed Ali; Chin, Siew Choo; Bao, Chao; Jolius, Gimbun (Elsevier Ltd., 2024)
This paper presents the mechanical characteristics and durability of concrete reinforced with basalt and bamboo fibres. The study involved testing specimens that were cured for varying durations ranging from 7 to 90 days, and subjecting the specimens to compressive, splitting, and tensile strength analyses. Four types of specimens were used, including control, bamboo fibre-reinforced concrete, basalt fibre-reinforced concrete, and a combination of both basalt and bamboo fibre-reinforced concrete. The durability of the concrete was evaluated through tests such as water absorption, acid attack, and water permeability. The results show that the optimum curing age is 60 days, and the hybrid fibre-reinforced concrete (HFRC) exhibited a higher compressive and flexural strength by 6.5% and 21.5% respectively, as compared to the control specimen. Moreover, HFRC had a 28.6% lower water permeability than the control specimen, implying higher durability. HFRC is also more resistant to acid attack, with a 3.9% reduction in weight loss compared to the control specimen. The post-acid attack test revealed that the HFRC has a compressive strength that is 21.8% higher than the control specimen. This study demonstrates that a hybrid of bamboo and basalt fibre can be used to produce a low-cost and eco-friendly concrete building material.